On Recognition of Contract Asset and Contract Liability in the Financial Statements (Global Journal of Management and Business Research, 2024)
With the publication of the International Financial Reporting Standard (IFRS) 15 "Revenue from Contracts with Customers", approaches to recognition and methods of measurement of the revenues have changed fundamentally.
Keywords: contracts; financial reporting; revenue from contracts with customers; contract asset; contract liability